2006
DOI: 10.1007/s00705-006-0755-6
|View full text |Cite
|
Sign up to set email alerts
|

Cowpea aphid-borne mosaic virus (CABMV) is widespread in passionfruit in Brazil and causes passionfruit woodiness disease

Abstract: Leaf samples of yellow passionfruit (Passiflora edulis f. flavicarpa) displaying fruit woodiness symptoms were collected in seven Brazilian states and the Federal District. Viral infection was confirmed by host range and ELISA, and fourteen viral isolates were obtained. All isolates were capable of infecting several leguminous host species, although differences in symptom severity were noticeable. Woodiness symptoms were reproduced in yellow passionfruit, and mosaic symptoms were induced in common bean. All is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 15 publications
4
40
1
10
Order By: Relevance
“…Although Nascimento et al (2006) demonstrated that CABMV isolates obtained from passion fruit caused systemic infections in cowpea, neither CABMV-PSevere or CABMV-PMild infected cowpea in the present study (Table 1). Similarly, Nascimento (2014) and Rodrigues et al (2015) demonstrated that isolates of CABMV-P obtained from passion fruit did not infect cowpea.…”
Section: Comparative Host Range Studies Of Cabmv Isolatescontrasting
confidence: 69%
“…Although Nascimento et al (2006) demonstrated that CABMV isolates obtained from passion fruit caused systemic infections in cowpea, neither CABMV-PSevere or CABMV-PMild infected cowpea in the present study (Table 1). Similarly, Nascimento (2014) and Rodrigues et al (2015) demonstrated that isolates of CABMV-P obtained from passion fruit did not infect cowpea.…”
Section: Comparative Host Range Studies Of Cabmv Isolatescontrasting
confidence: 69%
“…Passion fruit woodiness virus is caused by Cowpea aphidborne mosaic virus (CABMV) and is one of the diseases that affects passion fruit crops. It has impaired production in all regions where this fruit is cultivated (Nascimento et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, Del Polzo andLam (2003), like us, could not detect changes on growth of tobacco plants expressing baculovirus anti-apoptotic genes (iap or p35). The infection by CABMV is characterized by the development of deformed small hard fruits and also mosaic symptoms in leaves; infected plants show low yield of fruits and die sooner (Nascimento et al 2006). None of the transformed plants was resistant to CABMV, all of them showing the presence of chlorosis, mosaicism and leaf malformation (Fig.…”
Section: Discussionmentioning
confidence: 99%